Hubungan Perhatian Orangtua Terhadap Minat Belajar Murid Pada Pembelajaran Seni Budaya (Musik) Di Masa Pandemi Covid-19 Di SMP Negeri 2 Sijunjung - Kevin Bagaskara; Yos Sudarman (SENDRATASIK UNP, 2021)
This study aims to describe the role of parental attention to students' interest in learning cultural arts (music) during the Covid-19 pandemic at SMP Negeri 2 Sijunjung. The theoretical studies used in this study relate to the understanding of learning and learning; learning interests; parents' attention, and Cultural Arts Learning during the Covid-19 Pandemic. The research method used is quantitative research type with descriptive analysis approach. Based on the results of research that began from the exposure of environmental conditions where researching, the picture of parental attention to the learning activities of students at home, as well as the learning conditions of music arts in schools, it can be explained that based on the collection of data and processing of the rubric questions filled by parents and students in different intervals, where in the rubric asked 10 parents and 10 resource persons filled in the available fields according to the choice of answers , it was found that the result of the process of giving parental attention to the learning of students at home by 63%. While the interest of students to learn music at home is about 71%. If the two percentages are combined, a figure of 54%. This figure shows that there is a moderate level of connection between parents' attention to children's learning interests in sijunjung junior high school students who learn music online from home.